Análisis de la producción científica entorno a ODS 11: Ciudades y Comunidades Sostenibles - Carlos Alberto Gómez Cano; Alfredo Javier Pérez Gamboa; Verenice Sánchez Castillo (Mundo Fesc)
This article explores the scientific production related to Sustainable Development Goal 11 (SDG 11): Sustainable Cities and Communities, highlighting the importance of the psychosocial and governance transformations necessary to achieve these goals. Through a desk review approach, emerging trends in urban sustainability research are analyzed, including the need for a cultural shift toward sustainability and the adoption of more participatory and inclusive governance models. The study underscores that, beyond technological innovations and public policies, the success of the transition to sustainable cities depends on the integration of values ​​of cooperation, equity, and responsibility in society, as well as the implementation of governance mechanisms that actively involve all stakeholders in the decision-making process. This article provides a comprehensive view of the challenges and opportunities in creating sustainable cities, highlighting the need for holistic and collaborative approaches to achieving SDG 11.